Final answer:
To simplify the expression 6m²/9m² * 5/7m, first simplify the numerator and denominator separately. Then, multiply the fractions and simplify further.
Step-by-step explanation:
To simplify the expression 6m²/9m² * 5/7m, we can simplify each part separately. First, simplify the numerator: 6m²/9m² = 6/9 = 2/3. Then, simplify the denominator: 5/7m = 5/7 * 1/m = 5/7m. Now, we can rewrite the expression as (2/3) * (5/7m). Multiplying the fractions, we get (2 * 5)/(3 * 7m) = 10/21m. So, the simplified expression is 10/21m.